Frères et sœurs politiques. La fraternité à l'épreuve des femmes, 1789 – 1793 - Bérengère Kolly (Genre & Histoire)
Fraternity is an important notion to understand the exclusion of women from democracy and politics, as recent studies have shown. This is particularly the case in the French Revolution where fraternity was associated with politics, men and armed fighting. But conversely, what can be said about political sisters? The article uses two approaches to explore this concept: on the one hand, it seeks to disentangle “sisters” from their domestic enumeration – mothers, daughters, wives, sisters – in order to study them separately, in connection with brothers; on the other hand, it seeks to understand the political and philosophical signifiance of this sister figure. Contrary to brothers, sisters have to struggle with familial postures, which are suggested to women, in particular the mother figure. Nonetheless, their faintly discerned presence allows the emergence of a political space between women; they show the possible strength of sororal figures in brotherly political space.